Prediction and optimization of engine characteristics of a DI diesel engine fueled with cyclohexanol/diesel blends. Issue 16 (17th August 2020) - Gopal, Kaliyaperumal; Sathiyagnanam, A.P.; Rajesh Kumar, B.; Damodharan, D.; De Poures, Melvin Victor; Saravanan, S.; Rana, D.; Sethuramasamyraja, Balaji
ABSTRACT: This study uses cyclohexanol – a high-carbon, cyclic bio-alcohol which is a derivative of lignocellulosic biomass – in blended form with diesel to power a direct-injection single-cylinder diesel engine that is widely used in Indian agricultural sector. Experiments were conducted at the engine's rated load using the blend composition of cyclohexanol in diesel (10%, 20% and 30% by vol.), EGR (10%, 15%, and 20%) and injection timing (19°, 21° and 23°CA bTDC) as controllable factors. The optimization criterion is to minimize smoke, NOx emissions, and BSFC. Response surface methodology coupled with desirability approach was used to predict and optimize NOx, smoke opacity and BSFC measured from the experiments. The top solutions predicted by desirability approach were validated by confirmatory experiments and were found to describe the experimental data to a reasonable accuracy of within 4%. With reference to diesel operation, it was found that 10% by vol. of cyclohexanol/diesel blend injected at 21°CA bTDC and 10% EGR reduced NOx (43.1%▼) and smoke opacity (32.4%▼) with an increase in BSFC (4%▲). Cyclohexanol/diesel blend at optimum conditions delivered better smoke reduction but with higher NOx and slight increase in BSFC Cyclohexanol/diesel blends can be recommended as a full-time fuel to substitute diesel subject to long-term durability tests in diesel engines.